Latent Profiles of Parental Burnout During COVID-19: The Role of Child-Related Perceptions - Upadyaya, Katja; Salmela-Aro, Katariina (Frontiers in Psychology, 2021)
The present study examined latent profiles of parental burnout dimensions (e.g., exhaustion in parental role, contrast with previous parental self, feelings of being fed up, and emotional distancing, measured with a shortened version of the parental burnout assessment scale) among Finnish parents of sixth and eight grade children. In addition, the role of children’s strengths and difficulties (e.g., prosocial skills, hyperactivity, somatic problems, conduct problems, and peer problems), and parents’ growth mindset in predicting membership in the latent parental burnout profiles was examined. The participants were 1314 parents (80% mothers) from the Helsinki Metropolitan area who filled in a questionnaire concerning their parenting burnout and child-related perceptions during the fall 2020. The results were analyzed using latent profile analysis and three step procedure. Three latent profiles of parental burnout were identified: low parental burnout (85.7% of the parents), high parental burnout (8%), and emotionally distanced (6.3%) profiles. Parents who reported their children having some challenges (e.g., hyperactivity, somatic problems, conduct problems, and peer problems) more often belonged to the high burnout or emotionally distanced profiles rather than to the low parental burnout profile. Parents whose children had high prosocial skills and who employed growth mindset more often belonged to the low parental burnout rather than to the distanced profile.